Digital marketing : [strategy, implementation and practice] - Chaffey, Dave, 1963-; Ellis-Chadwick, Fiona (Pearson, 2022)
"Digital marketing has transformed how businesses and other organisations communicate with their audiences. Consumers now have access to a much wider choice of entertainment, products, services and prices from different suppliers and a more convenient way to select and purchase items. Organisations have the opportunity to expand into new markets, offer new services, interact with audiences in new ways and compete on a more equal footing with larger businesses. Marketers working within these organisations have the opportunity to develop new skills and to integrate these new tools to improve the competitiveness of the company"--